ANALISIS KUALITAS PELAYANAN PERIJINAN DI BPMPPT (BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU) KABUPATEN PEKALONGAN - Hesti Lestari (JURNAL ILMU SOSIAL, 2015)
Permitting is considered a very complicated, difficult and take a long time. Maind-seat it makes people reluctant to take care of permissions. Plus cases encountered either directly or indirectly, often distinguish social class. Quality services are closely related to customer satisfaction.This research was conducted in BPMPPT (Investment Board and Integrated Licensing Service) Pekalongan, using qualitative research methods, informants and people who take care of licensing related parties, selected purposively. Data retrieved through observation, in-depth interviews, and documentation. Research instruments: the researcher himself, and implementation process using tools: a tape recorder, interview guidelines and documents. Research to identify any implementation issues of licensing services. Data analysis is descriptive analysis using a technique Tri angulation.The result: BPMPPT have assessed IKM in 2012, 2013, and 2014; Results of the assessment in 2012: 76.50 score with a score of 74.0 in 2013 and 2014: a score of 73.8; These results indicate that during the three years from 2012 s / d 2014: decrease. Elements decreased: Getting Justice Services; Courtesy and hospitality Officer; Fairness Service Charge; Care Cost Certainty, Certainty and Security Services Schedule Services.